Effect of myelin water exchange on DTI‐derived parameters in diffusion MRI: Elucidation of TE dependence. Issue 3 (27th June 2017) - Lin, Mu; He, Hongjian; Tong, Qiqi; Ding, Qiuping; Yan, Xu; Feiweier, Thorsten; Zhong, Jianhui
Abstract : Purpose: Water exchange exists between different neuronal compartments of brain tissue but is often ignored in most diffusion models. The goal of the current study was to demonstrate the dependence of diffusion measurements on echo time (TE) in the human brain and to investigate the underlying effects of myelin water exchange. Methods: Five healthy subjects were examined with single‐shot pulsed‐gradient spin‐echo echo‐planar imaging with fixed duration (δ) and separation (Δ) of diffusion gradient pulses and a set of varying TEs. The effects of water exchange and intrinsic T2 difference in cellular environments were investigated with Monte Carlo simulations. Results: Both in vivo measurements and simulations showed that fractional anisotropy (FA) and axial diffusivity (AD) had positive correlations with TE, while radial diffusivity (RD) showed a negative correlation, which is consistent with a previous study. The simulation results further indicated the sensitivity of TE dependence to the change of g‐ratio. Conclusion: The exchange between myelin and intra/extra‐axonal water pools often plays a non‐negligible role in the observed TE dependence of diffusion parameters, which may accompany or alter the effect of intrinsic T2 in causing such dependence. The TE dependence may potentially serve as a biomarker for demyelination processes (e.g., in multiple sclerosis and Alzheimer's disease). Magn Reson Med 79:1650–1660, 2018. © 2017 International Society for Magnetic Resonance in Medicine.